2012
DOI: 10.1111/j.1469-0691.2011.03482.x
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniae: development of a mixed population of carbapenem and tigecycline resistance during antimicrobial therapy in a kidney transplant patient

Abstract: Nine isolates of Klebsiella pneumoniae were isolated from a renal transplant patient suffering from recurrent urosepsis over a period of 4 months. Imipenem resistance was detected after imipenem-ertapenem therapy. When treatment was switched to tigecycline the K. pneumoniae developed resistance to tigecycline (MIC = 8 mg/L). The nine isolates were tested by determination of agar dilution MICs, phenotypic carbapenemase, extended-spectrum beta-lactamases and metallo-beta-lactamase (MBL) testing and pulsed-field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…The mechanisms underlying this resistance have yet to be fully explored, but DL typing seems to indicate that tigecycline-resistant strains arose from the normal-phenotype parent strains isolated before tigecycline therapy. Our report suggests that first, in the Enterobacteriaceae, as has been reported for Gram-positive bacteria, development of resistance might be strictly related to antibiotic pressure (24,31). Second, the development of resistance might be associated with unsuccessful microbiological eradication when tigecycline is administered for infections where microorganisms are exposed to subinhibitory concentrations of the drug, such as UTI, septicemia, and abdominal abscess (7,12,17,23,32).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The mechanisms underlying this resistance have yet to be fully explored, but DL typing seems to indicate that tigecycline-resistant strains arose from the normal-phenotype parent strains isolated before tigecycline therapy. Our report suggests that first, in the Enterobacteriaceae, as has been reported for Gram-positive bacteria, development of resistance might be strictly related to antibiotic pressure (24,31). Second, the development of resistance might be associated with unsuccessful microbiological eradication when tigecycline is administered for infections where microorganisms are exposed to subinhibitory concentrations of the drug, such as UTI, septicemia, and abdominal abscess (7,12,17,23,32).…”
mentioning
confidence: 88%
“…Since then, 13 other cases have been reported, involving mostly A. baumannii and Klebsiella pneumoniae (2,3,9,12,15,20,23,24,28,30,32). Recently, Rodríguez-Avial et al reported the first detection of tigecycline resistance in SHV-12-producing K. pneumoniae during tigecycline treatment (24).…”
mentioning
confidence: 99%
“…Drug effectiveness, however, differs depending on the extent of spread of resistant isolates in each setting. Indeed, a growing number of studies indicate that the activity of these drugs is decreasing rapidly (7,21,80,85,88,96,128,142,151,156,185,186,226,243,247,275,277). In addition, rates of susceptibility to fluorinated quinolones are generally low, reflecting the multidrug-resistant nature of CPE.…”
Section: In Vitro Activitymentioning
confidence: 99%
“…Also, its low blood levels do not makes it an attractive drug for the treatment of vascularrelated infections [Falagas et al 2011]. Development of resistance was observed in vitro and in vivo in K. pneumoniae [Rodriguez-Avial et al 2012] and E. coli [Stone et al 2011]. Tigecycline has been used frequently in association with other drugs for the treatment of infections caused by extremely drug-resistant enterobacteria [Qureshi et al 2012;Tumbarello et al 2012].…”
Section: Other Antimicrobialsmentioning
confidence: 99%